International conference “Spaces for change in law, language, literature, history and cultural imagination of Asia, Africa and Europe”. 19th Conference of Translation, Interpreting, LSPs and Cultural Studies and 4th East European Consortium of Korean Studies (EECKS) and the International Conference on East Asian and Korean Studies. Gułtowy, 27th–29th June 2024. - Molęda, Bartosz (Glottodidactica, 2024)
International conference “Spaces for change in law, language, literature, history and cultural imagination of Asia, Africa and Europe”. 19th Conference of Translation, Interpreting, LSPs and Cultural Studies and 4th East European Consortium of Korean Studies (EECKS) and the International Conference on East Asian and Korean Studies. Gułtowy, 27th–29th June 2024.